Improvement of Gold Nanorods in Photothermal Therapy: Recent Progress and Perspective - Liao, Shengnan; Yue, Wang; Cai, Shuning; Tang, Quan; Lu, Weitong; Huang, Lingxiao; Qi, Tingting; Liao, Jinfeng (Frontiers in Pharmacology, 2021)
Cancer has been recognized as one of the most life-threatening diseases, and there is a significant need for novel technologies to treat cancer with an effective outcome and low toxicity. Photothermal therapy is a non-invasive therapeutic tool that transports nanomaterials into tumors, absorbing light energy and converting it into heat, thus killing tumor cells. Gold nanorods have attracted widespread attention in recent years due to their unique optical and electronic properties, and potential applications in biological imaging, molecular detection, drug delivery, especially in the photothermal treatment of cancer and other diseases. Herein, this review summarizes recent progress in synthesis methods and surface functionalization of gold nanorods for photothermal therapy. First, we introduced current major synthetic methods of gold nanorods and recently improved measures to reduce toxicity, increase yield, and control the particle's size and shape. Then, we summarized various surface functionalization approaches to construct a controlled drug release system, increase cell uptake, and improve the pharmacokinetics and tumor targeting effect, thus enhancing the photothermal effect of killing the tumor. At the end of the article, we proposed a brief outlook for the future development of gold nanorods' modification and functionalization in photothermal therapy.